2015
DOI: 10.1093/jxb/erv343
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in stress tolerance in dioecious plants: a critical appraisal in a physiological context

Abstract: Sex-related differences in reproductive effort can lead to differences in vegetative growth and stress tolerance. However, do all dioecious plants show sex-related differences in stress tolerance? To what extent can the environmental context and modularity mask sex-related differences in stress tolerance? Finally, to what extent can physiological measurements help us understand secondary sexual dimorphism? This opinion paper aims to answer these three basic questions with special emphasis on developments in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(92 citation statements)
references
References 91 publications
2
90
0
Order By: Relevance
“…While this result was against expectation, it suggests that apart from floral traits, gender is functionally and inherently neutral in both P. trichocarpa and P. balsamifera . This is all the more remarkable as sexual dimorphism in secondary sexual characteristics has been reported for many dioecious trees and shrubs, including poplars 5 . Finding equivalent patterns of trait variation between genders is unusual, but underscores that genetically-based sex does not necessarily result in inherent sexual dimorphism within a species.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…While this result was against expectation, it suggests that apart from floral traits, gender is functionally and inherently neutral in both P. trichocarpa and P. balsamifera . This is all the more remarkable as sexual dimorphism in secondary sexual characteristics has been reported for many dioecious trees and shrubs, including poplars 5 . Finding equivalent patterns of trait variation between genders is unusual, but underscores that genetically-based sex does not necessarily result in inherent sexual dimorphism within a species.…”
Section: Discussionmentioning
confidence: 53%
“…We tested whether inherent sex-based responses might exist depending on changing temperatures (as suggested by refs 3, 5 and 51), and specifically, whether spring phenology traits were altered by advancing spring temperatures through climate warming (e.g. ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3A), which suggests contrasting male and female reproductive strategies or functions. This contradicts the typical expectation that females of dioecious plants should be less stress-tolerant due to higher resource investment in reproduction (Juvany and Munné-Bosch, 2015). However, there is mixed evidence on the direction of sex-specific stress tolerance Three samples of a single genotype (1F) were used in each treatment level.…”
Section: Recoverymentioning
confidence: 84%
“…While most studies indicate that males have higher water stress tolerance than females (Juvany and Munné-Bosch, 2015), multiple examples of higher tolerance in females have been observed as well (Ward et al, 2002;S anchez-Vilas and Retuerto, 2009;Melanie et al, 2013). Further complicating matters, some studies have found that sex-linked differences in stress tolerance depend on life stage and environmental conditions (Rakocevic et al, 2009;Juvany and Munné-Bosch, 2015). Notably, higher DhT has been observed for females versus males in some bryophyte species (Newton, 1972;Stieha et al, 2014).…”
Section: Recoverymentioning
confidence: 99%